Proses Pembuatan Peraturan Daerah Terkait Pendidikan di Kabupaten Padang Pariaman - Muhammad Rayhan Pangestu (CV. ITTC INDONESIA, 2025)
The creation of Regional Regulations on education is a complicated process and involves many parties, including the executive, legislative, and community governments. This Perda aims to regulate, develop, and improve the quality of education in the region according to local needs and characteristics. The process of drafting the Perda on education begins with the planning stage, where academic studies and identification of education problems in the local environment are carried out. After that, the draft Perda will be submitted by the regional government or DPRD for further discussion through various mechanisms, such as public consultation and harmonization with higher regulations. After obtaining approval, the Perda is officially ratified by the regional head and begins to be enforced. However, in its implementation, various challenges often arise, such as budget constraints, coordination problems between agencies, and responses from the community. Therefore, periodic evaluation and synergy between the government, educational institutions, and the community are needed to ensure that the Perda is effective in improving the quality of education in the region.